Social imagination, abused memory, and the political place of history in Memory, History, Forgetting - Lythgoe, Esteban (2014)
In this paper we intend to show that in Memory, History, Forgetting Paul Ricoeur articulates memory and history through imagination. This philosopher distinguishes two main functions of imagination: a poetical one, associated with the interpretation and discourse, and a practical and projective one that clarifies and guides our actions. In Memory, History, Forgetting both functions of imagination are present but they are associated with different aspects of memory. The first one is present especially in the phenomenology of the cogni-tive dimension of memory, the second one is developed in the analysis of the abuses of the artificial memory, while the articulation between both of them is described in the section of the abuses of natural memory. Besides the similarities in the way these functions of imagination operate in Oneself as Another and in Memory, History, Forgetting, we will show some important differences between these two works and we will try to propose their reasons.